Improved Safety and Anti-Glioblastoma Efficacy of CAT3-Encapsulated SMEDDS through Metabolism Modification - Hongliang Wang (Molecules, 2021)
13a-(S)-3-pivaloyloxyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (CAT3) is a novel oral anti-glioma pro-drug with a potent anti-tumor effect against temozolomide-resistant glioma. 13a(S)-3-hydroxyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (PF403) is the active in vivo lipase degradation metabolite of CAT3. Both CAT3 and PF403 can penetrate the blood–brain barrier to cause an anti-glioma effect. However, PF403, which is produced in the gastrointestinal tract and plasma, causes significant gastrointestinal side effects, limiting the clinical application of CAT3. The objective of this paper was to propose a metabolism modification for CAT3 using a self-microemulsifying drug delivery system (SMEDDS), in order to reduce the generation of PF403 in the gastrointestinal tract and plasma, as well as increase the bioavailability of CAT3 in vivo and the amount of anti-tumor substances in the brain. Thus, a CAT3-loaded self-microemulsifying drug delivery system (CAT3-SMEDDS) was prepared, and its physicochemical characterization was systematically carried out. Next, the pharmacokinetic parameters of CAT3 and its metabolite in the rats’ plasma and brain were measured. Furthermore, the in vivo anti-glioma effects and safety of CAT3-SMEDDS were evaluated. Finally, Caco-2 cell uptake, MDCK monolayer cellular transfer, and the intestinal lymphatic transport mechanisms of SMEDDS were investigated in vitro and in vivo. Results show that CAT3-SMEDDS was able to form nanoemulsion droplets in artificial gastrointestinal fluid within 1 min, displaying an ideal particle size (15–30 nm), positive charge (5–9 mV), and controlled release behavior. CAT3-SMEDDS increased the membrane permeability of CAT3 by 3.9-fold and promoted intestinal lymphatic transport. Hence, the bioavailability of CAT3 was increased 79% and the level of its metabolite, PF403, was decreased to 49%. Moreover, the concentrations of CAT3 and PF403 were increased 2–6-fold and 1.3–7.2-fold, respectively, in the brain. Therefore, the anti-glioma effect in the orthotopic models was improved with CAT3-SMEDDS compared with CAT3 in 21 days. Additionally, CAT3-SMEDDS reduced the gastrointestinal side effects of CAT3, such as severe diarrhea, necrosis, and edema, and observed less inflammatory cell infiltration in the gastrointestinal tract, compared with the bare CAT3. Our work reveals that, through the metabolism modification effect, SMEDDS can improve the bioavailability of CAT3 and reduce the generation of PF403 in the gastrointestinal tract and plasma. Therefore, it has the potential to increase the anti-glioma effect and reduce the gastrointestinal side effects of CAT3 simultaneously.